Structural system collapse risk limitation strategy - Pichugin, Sergiy; Klochko, Lina (Academic journal Industrial Machine Building Civil Engineering, 2020)
This article presents a general strategy for limiting the structural system risk collapse a using the real construction object example. In the course of the work, an analysis of possible accident scenarios at a construction site was carried out. A statistical data analysis is presented to create the most systematic method for the possible accident scenario in construction. The article presents the calculations results of the building frame spatial model for progressive structure destruction to determine the accident possibility. When changing the monolithic floor geometry and removing the columns, the failure probability of the supporting structures and the consequences to which this accident could lead were considered. Also, in this work, the economic consequences question is raised. The scheme calculation result is presented and the corresponding conclusions are drawn
Keywords: statistics; modeling; accident; building; probability of an accident; destruction; consequences; systematization